Hypercoagulability and Biochemical Markers in Thrombosis and Stroke - kasro, Vian ahsan; Dawood, Zahraa Khudhair; Abdullah, Estabrak kareem; mohsein, Osama A. (American Journal of Biology and Natural Sciences, 2025)
Hypercoagulability, a state of increased blood clotting potential, plays a critical role in the pathophysiology of thrombotic events, including ischemic stroke. It results from an imbalance between procoagulant and anticoagulant factors, often driven by underlying conditions such as inflammation, malignancy, genetic mutations (e.g., Factor V Leiden), or metabolic disorders. This review aims to highlight the association between hypercoagulability and the development of thrombosis and stroke, with a specific focus on emerging biochemical markers that may aid in early diagnosis, risk stratification, and therapeutic monitoring. Key biomarkers implicated in hypercoagulability include D-dimer, fibrinogen, thrombin-antithrombin complexes, and P-selectin, all of which reflect ongoing coagulation activation and fibrinolysis. Inflammatory mediators such as C-reactive protein (CRP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) have also been shown to contribute to the prothrombotic milieu by activating endothelial cells and platelets. Furthermore, alterations in lipid profiles, elevated homocysteine levels, and impaired fibrinolytic activity are associated with increased stroke risk in hypercoagulable patients. Understanding the interplay between hypercoagulability and these biomarkers is essential for improving clinical outcomes. Their measurement may enhance early detection of thrombotic risk and support the tailoring of anticoagulant therapies in high-risk individuals. Current research is exploring novel markers and genetic predictors to further refine stroke prediction models. In conclusion, hypercoagulability and its associated biochemical markers are central to the development and progression of thrombosis and stroke. Further studies are needed to validate the clinical utility of these markers in routine practice and to guide personalized therapeutic strategies.